Creation of D.R.T.B Works for Guitar Major Students Who Participate in the Jakarta Six String Extracurricular in the FBS UNJ Music Education Study Program - Aprianno, Ryan Gredy; Torondek, Timothy Revival April (CV. Publikasi Indonesia, 2025)
The increasing challenge faced by guitar major students in mastering classical guitar techniques highlights the need for innovative approaches in music education. Many students transitioning from acoustic or electric guitars struggle with fundamental classical guitar techniques such as posture, hand positioning, and specific playing techniques like tirando and pizzicato. This research aims to address these challenges by developing a structured approach to creating classical guitar ensemble works tailored for the Jakarta Enam Senar extracurricular group. The importance of this research lies in its potential to enhance the compositional and performance skills of students, fostering their ability to contribute to ensemble repertoires and strengthening their understanding of classical guitar techniques. The study employs a qualitative research method with a case study approach, complemented by Practice Led Research to bridge theoretical and practical knowledge. Techniques such as composition workshops, expert-led discussions, and iterative practice sessions were utilized to refine the students' skills. The findings demonstrate significant improvements in the students' ability to create and perform classical guitar ensemble works. The research concludes that structured creative practices and theoretical grounding are essential for overcoming technical challenges and inspiring innovation in music education. These results contribute to the development of effective pedagogical strategies for classical guitar education and provide a model for integrating creative practices into music curriculums.